Solid non-rinse animal shampoo - Abdul Rahim, Muhammad Akram (2016)
In this study, non-rinse animal shampoo was formulated into solid powder using spray drying techniques. The morphology, angle of repose, bulk density and tapped density of powder, as well as, the physical appearance, pH, surface tension, viscosity and foaming ability of the rehydrated shampoo were characterized. In vivo (skin sensitivity and eye irritation test) were conducted to evaluate the safety of the shampoo while functional test was performed with the aid of microscopic imaging and scanning electron microscopy. Solid non-rinse animal shampoo had generally good powder flow property. Rehydrated shampoo showed no oil-phase separation, low stickiness and quick drying after several lathering. The rehydrated shampoo exhibited mild to none irritation to animal eyes and skin. The washing action of rehydrated shampoo in removing dirt and sebum from animal fur and skin was good and similar to the commercial shampoo capability.